2015
DOI: 10.1371/journal.pone.0134139
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein, a Bioflavonoid, Prevents Cisplatin-Induced Acute Kidney Injury by Up-Regulating Antioxidant Defenses and Down-Regulating the MAPKs and NF-κB Pathways

Abstract: Acute renal failure is a serious complication of the anticancer drug cisplatin. The potential role of baicalein, a naturally occurring bioflavonoid on cisplatin-induced renal injury is unknown. Here, we assessed the effect of baicalein against a murine model of cisplatin-induced acute renal failure and investigated the underlying possible mechanisms. Renal function, kidney histology, inflammation, oxidative stress, renal mitochondrial function, proteins involved in apoptosis, nuclear translocation of Nrf2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 53 publications
5
80
0
1
Order By: Relevance
“…The proposed mechanism of anthracycline-induced organ damage includes the generation of reactive oxygen species, inflammation, caspase activation and apoptosis (Sahu et al, 2014(Sahu et al, , 2015. Our previous research has suggested that the activation of the nuclear factor-κB (NF-κB) pathway is involved in the development and progression of epirubicin-induced hepatotoxicity and reactive oxygen species play a crucial role in aggravating inflammation by activating the NF-κB pathway (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism of anthracycline-induced organ damage includes the generation of reactive oxygen species, inflammation, caspase activation and apoptosis (Sahu et al, 2014(Sahu et al, , 2015. Our previous research has suggested that the activation of the nuclear factor-κB (NF-κB) pathway is involved in the development and progression of epirubicin-induced hepatotoxicity and reactive oxygen species play a crucial role in aggravating inflammation by activating the NF-κB pathway (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are numerous side effects associated with this type of treatment (5). Baicalein has been proposed in several extensive studies as a potential candidate for the treatment of cancer (14,15,18). In the present study, the effect of cisplatin combined with baicalein (a flavonoid component isolated from the root of traditional Chinese medicine SB) on cytotoxicity and apoptosis of human lung cancer cells A549 was examined.…”
Section: Discussionmentioning
confidence: 97%
“…SB is currently recognized as a novel anti-cancer drug and chemotherapy adjuvant (10)(11)(12). Baicalein is one of the bioactive flavonoid components isolated from the root of SB, and it has been revealed to account for the majority of cytotoxicity of SB for a range of cancer cell lines in vitro (13)(14)(15). Molecular studies in other human cell lines have demonstrated that these flavonoid compounds possess potent cell cycle arresting and apoptotic properties (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that baicalein increases the cytotoxicity of cisplatin [18]. It has also been demonstrated that baicalein prevents cisplatin-induced renal damage in mice [19]. However, to the best of our knowledge, the effect of baicalein in hepatoprotection during cisplatin administration has not been reported so far.…”
Section: Introductionmentioning
confidence: 91%